Management models of changes – the empirical study in Slovak companies - Sujová, Andrea; Simanová, Ľubica (Business, Management and Economics Engineering, 2022)
Purpose – Change management depends on the type and extent of the implemented change. The aim of the paper is to identify management model of changes in Slovak enterprises and to define conditions of effective change management for the prevailing type of changes. Research methodology – The main method of the research was primary quantitative research via questionnaires. Outputs from the questionnaires were evaluated by statistical methods, pivot tables, and chi-square test. Findings – Slovak enterprises apply functional approach to change management based on financial improvement. Mostly performed changes are operative. The success of changes can increase focus on improvement of internal processes, force field optimization and project elaboration via log frame. Research limitations – The limitations of the research consist in a chosen quantitative method which doesn’t enable discovery of a qualitative and psychological sides of managing changes and the research sample including mostly small sized enterprises in Slovakia. Practical implications – The detected conditions of an effective change management can inspire the enterprises to increase the success by implementation of changes. Originality/Value – New empirical knowledge concerning change management in the practise of Slovak enterprises, identification of the applied model by managing the changes and conditions for an effective management of changes.